Scenic Processes: Light as a guiding element of scenic visuality based on the analysis of a scenic experiment (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This research is an analysis of a theatrical experiment that aims to understand how the visuality of light enters the performance as a complementary factor of the scene, focusing on the theatrical experiment entitled "Interrogation Room," conducted in the Lighting course of the Degree in Theatre at the Federal University of Maranhão (UFMA) during the 2022.4 vacation period. With a careful researcher's eye and based on bibliographic research, I analyzed the connections between how the light was conceived in harmony with the presented scene. Throughout this work, we explore not only the concept of the visuality of stage lighting but also seek to understand how light is used to create atmosphere, highlight elements, influence the audience's emotional perception, and the creative inventions through makeshift lighting solutions.